Studi Tingkat Keberhasilan Penangkapan dan Keragaman Jenis Tikus di Pasar Oeba dan Pasar Oesapa Kota Kupang - Toha, Larry Richard Wellem; Inna, Angelina Monika T.; Laga, Laura Katharina Lengga (Jurnal Veteriner Nusantara, 2025)
The market is a public place that is used as a meeting place between sellers and buyers to conduct transactions. Traditional markets are markets that have not paid attention to health principles such as environmental sanitation. Poor sanitation plays a role in increasing the breeding of vectors such as rats. This study aims to measure the success rate of catching rats using roasted coconut, salted fish, and sweet potato bait, identify the types of rats that have been caught in the market, and analyze the relationship between the sanitation of the market and the success rate of catching rats and the level of rat density. This type of research is a descriptive study with market observation methods, collection of rat samples and identification of rat morphology. The total traps used in each market were 24 traps for 6 days at 8 points indicated by rats. At the Oeba market, rats prefer salted fish bait with a success rate of 25%, then roasted coconut with a success rate of 16% and sweet potatoes with a success rate of 2%. At the Oesapa market, rats preferred salted fish bait with a success rate of 29%, then roasted coconut with a success rate of 17% and sweet potatoes with a success rate of 3%. There are 5 types of rats and 1 type of shrew that have been caught, namely the house rat (Rattus tanezumi), the wirok rat (Bandicota indica), the rat rat (Rattus norvegicus), the bush rat or tree rat (Rattus tiomanicus), the field rat (Rattus exulans) and House shrew (Suncus murinus). Sanitation in the Oeba market and Oesapa market is included in the poor category so that the level of rat density in the Oeba market and Oesapa market is relatively high with percentages of 14% and 16% respectively.